2008
DOI: 10.1037/a0013316
|View full text |Cite
|
Sign up to set email alerts
|

It's a wonderful life: Mentally subtracting positive events improves people's affective states, contrary to their affective forecasts.

Abstract: The authors hypothesized that thinking about the absence of a positive event from one's life would improve affective states more than thinking about the presence of a positive event but that people would not predict this when making affective forecasts. In Studies 1 and 2, college students wrote about the ways in which a positive event might never have happened and was surprising or how it became part of their life and was unsurprising. As predicted, people in the former condition reported more positive affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 42 publications
3
79
0
1
Order By: Relevance
“…Similarly, thinking about how a positive outcome was surprising and might never have happened led to more positive affect than thinking about how the outcome actually did happen and was unsurprising (Koo, Algoe, Wilson, & Gilbert, 2008). In contrast, writing about positive life events in a systematic and analytical way reduced positive emotion compared to simply thinking about the events (Lyubomirsky, Sousa, Dickerhoof, 2006).…”
Section: How Social Sharing May Increase and Sustain Positive Emotionmentioning
confidence: 96%
“…Similarly, thinking about how a positive outcome was surprising and might never have happened led to more positive affect than thinking about how the outcome actually did happen and was unsurprising (Koo, Algoe, Wilson, & Gilbert, 2008). In contrast, writing about positive life events in a systematic and analytical way reduced positive emotion compared to simply thinking about the events (Lyubomirsky, Sousa, Dickerhoof, 2006).…”
Section: How Social Sharing May Increase and Sustain Positive Emotionmentioning
confidence: 96%
“…Spanning both ends of the emotional spectrum, counterfactual thinking can produce not only regret but also gratitude. Recent research has shown that mentally subtracting positive events from one's life can actually increase positive affective states (Koo, Algoe, Wilson, & Gilbert, 2008) through a process akin to "counting one's blessings. "…”
Section: Counterfactual Reflections On the Pastmentioning
confidence: 99%
“…In one study, participants instructed to contemplate what life would be like without a particular positive event reported higher wellbeing than those not instructed to mentally subtract (Koo, Algoe, Wilson, & Gilbert, 2008). In particular, participants who imagined their lives if they had never met their romantic partner reported higher relationship satisfaction than those who did not mentally subtract their relationship.…”
Section: Cultivate Appreciationmentioning
confidence: 99%